Building and managing e-book collections : a how-to-do-it manual for librarians - Kaplan, Richard, 1954- (How-to-do-it manuals for libraries, 2012)
Offering multiple perspectives from electronic resource professionals at world-renowned libraries such as Harvard, the University of Michigan, Duke, and Northeastern, this book provides a comprehensive and well-rounded e-book education. Success stories highlight each chapter's lessons, giving you real-world examples of effective e-book implementation in both school and public libraries.